Liturgi: Menumbuhkan Harapan dan Pembebasan - Kusuma, Yoseph Indra (Lux et Sal, 2025)
This study examines the role of liturgy in fostering hope and liberation within the Catholic faith, inspired by Romano Guardini’s The Spirit of the Liturgy. Liturgy is often misunderstood in two extremes: as rigid rules that restrict spiritual freedom or as a celebration devoid of structure. This research aims to explore liturgy as a "sacred play" that harmonizes order and freedom, seriousness and joy, structure and spiritual expression. The study employs a qualitative approach with a literature review method, analyzing primary theological texts, including Guardini’s work, official Church documents, and contemporary scholarly discussions on liturgical theology. Data collection involves textual analysis of liturgical norms, theological interpretations, and historical developments in liturgical praxis. The study applies a categorical framework—Necessary and Unnecessary, Proper and Improper, Fitting and Unfitting—to evaluate how liturgy shapes spiritual liberation and eschatological hope. Findings reveal that true liturgical freedom is not the absence of rules but the structured encounter with God that liberates believers from worldly constraints. The study highlights the eschatological dimension of the liturgy, wherein each Eucharistic celebration not only commemorates past salvation but also anticipates the fulfillment of God’s Kingdom. Pastoral implications emphasize the need for proper liturgical education, the role of clergy and lay ministers in preserving the sacredness of the celebration, and the importance of maintaining liturgical beauty and reverence to deepen the faithful’s spiritual experience. The study concludes that a richer understanding of liturgy allows believers to participate in the celebration not as a mere obligation but as a transformative encounter with God, leading to authentic hope and liberation in Christ.